(untitled) (AYUSHDHARA, 2018)
Vitiligo occurs when the cells that produce melanin die or stop functioning. Vitiligo affects people of all skin types, but it may be more noticeable in people with darker skin. The condition is not life-threatening or contagious. It can be stressful or make you feel bad about yourself. Some dermatological outpatient records show the incidence of vitiligo to be 3% to 4% in India although an incidence as high as 8.8% has also been reported. In the Indian states of Gujarat and Rajasthan, the prevalence of vitiligo is very high being described by some as of epidemic proportions. Sthana of Brajaka pitta is Twak and should be maintained in proper state, imbalance to this may lead to skin diseases. Shvitra is caused by various dietetic and behavioural factors which aggravate the Tridoshas, especially the Kapha dosha vitiating the Raktha, Mamsa and Meda Dhatu. Here present case a 16 year old boy, who came to our OPD with c/o white patches around the B/L eyes, forearms, elbow and middle malleolus since 1 year. “Dhatryadi Kwatha”-50ml., “Mahakhadiradi Ghrita” 10ml. and “Gunjaphaladi Lepa” (for external application) were given for 3 months.